The Effect of Product Promotion Strategy and Service Quality on Customer Satisfaction with Social Media as an Intervening Variable for Bank Syariah Indonesia Customers at UIN K.H. Abdurrahman Wahid Pekalongan - Imani, M. Fathrezza; Adinugraha, Hendri Hermawan (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2023)
The position of humans as social beings in meeting their needs cannot be produced by the individual himself. Therefore he needs to work together and needs help with others, one of which is an Islamic Financial Institution. As a result, Islamic Financial Institutions here have an important role in today's modern economy and to assist people in meeting their needs. Along with changing patterns of competition, a company requires an assessment of the elements that can affect its competitive ability to achieve the goals implemented, including Indonesian Sharia Banks that are included in the scope of Islamic Financial Institutions. This type of research is field research with a quantitative research approach. The population in this study are BSI customers who are domiciled in the former Pekalongan Residency area. While the sampling was carried out according to the Lemeshow formula with a total sample of 200 respondents. Sources of data in this study are primary data and secondary data. Data collection method used is the distribution of questionnaires. And the method of analysis used is through Path Analysis, where the Social Media variable is positioned as an intervening variable. Based on the research results, two path test equations were obtained. The result of testing these two equations is that there is an influence on the two independent variables used, namely the Product Promotion Strategy and Service Quality variables on Customer Satisfaction, either directly or indirectly through the Social Media variable. Keywords: Product Promotion Strategy, Service Quality, Customer Satisfaction, Social Media.